The role of SIRT1 in the process of Toxoplasma gondii infection of RAW 264.7 macrophages - Dong, Kai; Jiang, Ziyang; Zhang, Jianhui; Qin, Hanxiao; Chen, Jianping; Chen, Qiwei (Frontiers in Microbiology, 2022)
Toxoplasma gondii is an opportunistic pathogenic protozoan that can infect almost all kinds of warm-blooded animals including human beings.T. gondii can evade the host’s immune response, a process known as immune evasion. Our main objective was to evaluate the role played by SIRT1 (one of the sirtuins (SIRTs) that are a family of nicotinamide adenine dinucleotide (NAD)-dependent histone deacetylases (HDACs)) in T.gondii infection of RAW264.7 macrophages. In this study, we evaluated and observed alterations in the activity, expression and localization of SIRT1, assessed its involvement in the CD154/IFN-γ killing pathway and in autophagy during T. gondii infection. Inhibition of SIRT1 in host cells effectively reduced the number of intracellular tachyzoites, and the mechanism behind this effect might be the upregulation of IRGM1 and initiation of autophagy. To the best of our knowledge, our study is the first to prove that T. gondii infection upregulates SIRT1 in RAW 264.7 cells, and inhibition of SIRT1 reduces the number of intracellular tachyzoites. Moreover, upregulation of IRGM1 and activation of autophagy may contribute to the intracellular inhibition of T. gondii caused by SIRT1 inhibition.